Normative Production Accounting in the Digital Economy: Issues and Solutions - Polulekh, M. V. (Accounting. Analysis. Auditing, 2018)
In the digital economy the task of real-time monitoring of the state of production chains creates an objective need to restore normative economy. Detailed study of normative production accounting becomes particularly relevant and significant. The aim of the study was to classify the issues of normative production accounting and to justify the ways of solving them for further standardization and regulation of analytical procedures. Empirical methods such as observation, comparison, induction and deduction were used in the study. The article reports the results of the retrospective analysis of the provisions and practices of the normative method as well as the state of the deployment of the production operations and chains in the current context. It was determined that the formula for the normative method requires modification while the algorithm for allocation of indirect costs requires justification and interpretation. The study concludes that theoretical and methodological provisions of the normative method should be developed regarding the business processes. The set of characteristics which determines competitiveness of business processes was argued as the accounting object. Basing on this it was proven that there is need for further development of national standards for statistics, metrology, accounting as well as for the use of a common classification of industries and typology of production.